Dampak IFRS 15 Bagi Laporan Keuangan Perusahaan Konstruksi - Moch Yasin Dwi Ervinda; Muhammad Hadiyan Ridho (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2020)
This study aims to analyze the impact of the implementation of IFRS 15 associated with the recognition of contract revenue with customers at the Boygues SA company in France. The research method used in this study is a qualitative method. The steps taken in this study by using content analysis that is collecting data, documenting and analyzing. This study uses the 2017 financial statements before and after implementation of IFRS 15 as a basis for evaluating the impact from those implemetation. The results showed that the application of IFRS 15 did not significantly influence the company's revenue or overall Financial Report.